PENGARUH PENAMBAHAN ABU ARANG TEMPURUNG KELAPA TERHADAP KUAT TEKAN PAVING BLOCK - A, Arman; Mulyati, Mulyati; Wardi, Syafri; Roza, Angelalia; Sonia Putra, Didi (Jurnal Teknologi dan Vokasi, 2023)
Paving Block is a building material made from a mixture of cement, sand and water. Paving blocks are widely used in the construction sector, such as sidewalks, highways, parking lots, parks and others. Ease of installation, inexpensive maintenance and fulfilling aspects of beauty make paving blocks more preferred. Along with the many developments such as houses, parks, roads in the midst of today's society, this has resulted in the need for paving blocks increasing. Because the hardening process takes quite a long time, therefore, to speed up hardening, this study added coconut shell ash. In this study using a ratio of 1 Pc: 3 Ps and the addition of coconut shell ash with variations of 0%, 2.5%, 5% and 7.5% by weight of cement. The average compressive strength value of paving block plans is a minimum of 12.5 MPa and a maximum of 15 MPa for grade C which is used for pedestrians and other uses, with rectangular specimens measuring 20 cm x 10 cm x 6 cm of 24 pieces with age 28 days testing for compressive strength and water absorption test. Based on the test results, the normal compressive strength of paving blocks was 13 MPa, the addition of 2.5% coconut shell ash was 13.5 MPa, 5% shell ash was 14.5 MPa, the addition of 7.5% coconut shell ash was 12. .83 MPa. Based on the test results, the normal Paving Block water absorption value was 7.8%, 2.5% shell ash was 7.22%, the addition of 5% shell ash was 6.3%, 7.5% shell ash was 4.89%. Thus, it can be stated that the effect of Coconut Shell Ash can increase compressive strength and reduce water absorption. The highest compressive strength and lowest water absorption were obtained at the addition of 5% for the compressive strength and the lowest water absorption was obtained at the addition of 4.89%.